Inhibition of steel corrosion by some schiff and mannich bases: A theoretical evaluation - Gece, Ender Gökhan (Ukrainian State University of Chemical Technology, 2021)
There is no doubt that the value and importance of using computational methods in corrosion science are becoming gradually recognized. Drilling deeper into the thought that certain molecular electronic descriptors such as ionization potential, electron affinity, HOMO-LUMO gap and dipole moment matter, because they present a unique solution to comprehend the inhibition properties of corrosion inhibitors, leads us to a further quandary. The reliability of such parameters is the subject of acrimonious debate, and thus, the present study is an extension of this attempt to contemplate earlier experimental results reported for some Schiff and Mannich bases as corrosion inhibitors for steel in neutral aqueous solutions by using density functional theory calculations. Due to the sources of uncertainties like the structure of the molecular model, the description of environmental efforts and errors related to the nature of quantum chemical methods, it was inferred that no coherent picture could be emerged about the corrosion inhibition properties of the studied compounds through calculated descriptors. © 2021 Ukrainian State University of Chemical Technology.
Keywords: Carbon steel; Corrosion; Density functional theory; Inhibitor; Mannich base; Schiff base